Reed Solomon encoder & decoder, 16 Quadrature amplitude modulation (QAM) on of DM transceiver [electronic resource] - Calub Tan, 1989-; Muhammad Nadzir Marsono (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mikroelektronik)) - Universiti Teknologi Malaysia, 2011